Personal Development of Doctoral Students - Deborah M. Riby; Simon Rees (Encyclopedia, 2024)
Personal development refers to the process of increasing one’s self-awareness, associated increases of self-esteem, increasing skills, and fulfilling one’s aspirations. The current paper reflects on these elements within the doctoral journey, for PhD students within the UK Higher Education system. The paper makes particular reference to frameworks to encourage and capture personal development needs and supervision or coaching styles that may be used to encourage a continual reflection of personal development throughout the doctorate.